Comparative efficacy of moxibustion as an add-on treatment with different durations for diabetic peripheral neuropathy: study protocol for a randomized controlled trial - Kang, Yurong; Hu, Hantong; Lin, Can; Zheng, Yu; Jiang, Minjian; Wei, Zhouyuan; He, Xiaofen; Fang, Jianqiao; Jiang, Yongliang (Frontiers in Neurology, 2025)
BackgroundDiabetic Peripheral Neuropathy (DPN) can markedly diminish patients’ quality of life. Current treatments provide limited relief, driving interest in non-invasive options such as moxibustion. Moxibustion, a technique rooted in acupuncture, shows promise for managing pain. However, it lacks standardized protocols for treating DPN, especially concerning moxibustion duration, and its effectiveness for DPN is not well-supported by evidence. Thus, this study seeks to identify the optimal moxibustion duration to relieve DPN symptoms and enhance nerve function, filling an important gap in clinical practice.MethodsParticipants will be randomly allocated to three clinical centers, with 30 individuals at each center, and evenly divided among the conventional treatment group, the 15-min moxibustion group, and the 30-min moxibustion group. The conventional treatment group will be administered mecobalamin and epalrestat for a duration of 4 weeks, while the moxibustion groups will receive moxubustion as an add-on therapy treatment twice a week over the same period. The duration of moxibustion differs from the 15-min group, while the procedure remains consistent across the moxibustion groups. The primary outcome is total clinical effectiveness. The second outcomes include electrophysiological examination, the Toronto Clinical Scoring System (TCSS), the Visual Analogue Scale (VAS), the Traditional Chinese Medicine Syndrome Score Scale (TCMS), and infrared thermography testing. The outcomes will be assessed during the baseline period, after the 8th treatment, and at the one-month follow-up.ConclusionThis trial aims to identify the optimal moxibustion duration for DPN symptom relief and nerve function improvement, offering evidence for standardized clinical protocols. The findings could enhance treatment efficacy, reduce adverse effects, and alleviate DPN’s socio-economic burden.Clinical trial registrationhttps://clinicaltrials.gov/, NCT06330233.